Strengthening of Ties between the Russian Orthodox Church and the Orthodox Church of Cyprus as an Important Task of the Department for External Church Relations in 1960–1972 - Archpriest Sergey L. Zvonarev (Вестник Екатеринбургской духовной семинарии)
This article explores the relations between the Russian Orthodox Church and the Orthodox Church of Cyprus from 1960 to 1972, during the tenure of Metropolitan Nikodim (Rotov) as the Head of the Department for External Church Relations. Drawing on previously unpublished materials from church and state archives including the Archive of the Department for External Church Relations, the Archive of Foreign Policy of the Russian Federation, the State Archive of the Russian Federation, and the Russian State Archive of Contemporary History as well as the sources published in the “Journal of the Moscow Patriarchate” and the newspaper “Izvestia”, the author examines various aspects of bilateral church contacts. In the relations between the hierarchies of the Russian Orthodox Church and the Orthodox Church of Cyprus, a key factor was the fact that Archbishop Makarios of Cyprus also held the office of President of the Republic of Cyprus, giving church contacts a political dimension. This aspect was significant for Soviet diplomacy, which viewed close inter-church ties as means of strengthening Soviet-Cypriot relations. Metropolitan Nikodim was fully aware of this feature of church-state cooperation and sought to maintain communication with Archbishop Makarios. The article discusses the Moscow Patriarchate’s support for the leadership of the Church of Cyprus and, simultaneously, for the Cypriot state during moments of political tension in the Republic, as well as for its assistance to individual representatives of the Church of Cyprus. The Church hierarchs in Moscow closely followed the process of rapprochement between Greece and Cyprus with the prospect of their unification (enosis), supporting the exchange of church delegations, promoted academic cooperation, and facilitated the participation of official church representatives in public relations between the two countries. The fact that hierarchs of the Moscow Patriarchate held positions in the governing bodies of the “USSR — Cyprus Friendship Society” reflected the recognition of the Russian Church’s role in Soviet public life, particularly in the sphere of international affairs. According to the author, student exchanges did not play any significant role in the cooperation agenda of the two Churches, which can be attributed to objective reasons.